Research and development of alkali earth tungstate and molybdate crystal scintillators for search for rare events - Nagornaya, L.L.; Dubovik, A.M.; Grinyov, B.V.; Katrunov, K.A.; Tupitsyna, I.A.; Vostretsov, Yu.Ya. (Functional Materials, 2009)
Large volume ZnWO₄ scintillator with improved performance characteristics have been obtained. Due to its favorable light yield values at low temperatures and extremely low intrinsic radioactivity, zinc tungstate is a material of very good prospects for cryogenic double beta-decay and dark matter experiments. The ZnMoO₄ single crystals were produced for the first time using Czochralski technique. The suitability of this material for cryogenic rare event search experiments has been studied and identified the ways to improve the scintillation properties of the crystal have been outlined. The manufacturing methods of MgWO₄ crystals have been investigated and the manufacturing possibility by pulling from the solution-melt on a seed has been established. The experimental MgWO₄ single crystals of ca. 1 cm³ volume have been prepared for the first time and the luminescence and scintillation characteristics thereof have been measured.